New life for archaeological collections - Allen, Rebecca, 1964-; Ford, Ben M. (Society for Historical Archaeology series in material culture., 2019)
"New Life for Archaeological Collections explores and provides strategies for addressing what archaeologists have increasingly perceived as the "curation crisis," that is, too much stuff with too little interpretation and analysis"--